Neoantigen Vaccine Delivery for Personalized Anticancer Immunotherapy - Guo, Yugang; Lei, Kewen; Tang, Li (Frontiers in Immunology, 2018)
Cancer neoantigens derived from random somatic mutations in tumor tissue represent an attractive type of targets for the cancer immunotherapies including cancer vaccine. Vaccination against the tumor-specific neoantigens minimizes the potential induction of central and peripheral tolerance as well as the risk of autoimmunity. Neoantigen-based cancer vaccines have recently showed marked therapeutic potential in both preclinical and early-phase clinical studies. However, significant challenges remain in the effective and faithful identification of immunogenic neoepitopes and the efficient and safe delivery of the subunit vaccine components for eliciting potent and robust anticancer T cell responses. In this mini review, we provide a brief overview of the recent advances in the development of neoantigen-based cancer vaccines focusing on various vaccine delivery strategies for targeting and modulating antigen presenting cells. We discuss current delivery approaches including direct injection, ex vivo pulsed dendritic cell vaccination, and biomaterial-assisted vaccination for enhancing the efficiency of neoantigen vaccines and present a perspective on future directions.